SOCIAL MEDIA DISCOURSE AND THE TRANSFORMATION OF LITERARY CRITICISM - Oliver Bennett (International Journal of Literature and Language Studies, 2026)
This article examines how social media platforms transform practices of literary criticism. The study responds to the problem that literary criticism has expanded beyond academic journals and newspapers, but platform-based reading communities are still sometimes dismissed as superficial rather than analyzed as critical cultures. Using digital discourse analysis with attention to participation, evaluation, and platform affordances, the article analyzes public posts, comments, and review threads from online reading communities. The findings indicate that social media criticism favors affective immediacy, recommendation networks, short-form interpretation, and identity-based reading, while also creating new hierarchies of visibility. The article argues that digital literary criticism should be evaluated as a changing ecology of public reading rather than a simple decline from professional criticism. By connecting language, literary form, and interpretation, the study offers a concise contribution to current debates in literature and language studies.